2021
DOI: 10.1109/access.2021.3095306
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Error-Increasing Factors by Sensor Response-Based Localization Technology Through Real Device Experiments

Abstract: A sensor response-based localization technology that uses the non-geotagged responses of environmental object detection sensors to estimate the positions of sensors in a defined observation area was proposed in a previous study. That method is based on the concept that the proximity relationships among sensors obtained from the closeness of the sensor response times or collected data similarities. However, since that study was limited to simulation-based experiments, this study extends the scheme to experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…• We confirmed that the sensor response-based localization method [10], [11] for WSNs could be applied to indoor localization. • Through simulation experiments, we found that the proposed methods could obtain comparable accuracy to existing methods when the attenuation model is accurate.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…• We confirmed that the sensor response-based localization method [10], [11] for WSNs could be applied to indoor localization. • Through simulation experiments, we found that the proposed methods could obtain comparable accuracy to existing methods when the attenuation model is accurate.…”
Section: Introductionsupporting
confidence: 63%
“…In these simulation experiments, we assumed that the average strength of the radio signal from a pedestrian's smartphone or an anchor node at a distance of 𝑑 is determined by (11). Note that radio signals in an actual environment are affected by fading.…”
Section: Simulation Experiments and Discussion A Simulation Conditionsmentioning
confidence: 99%
See 3 more Smart Citations